Hierarchical SrTiO3/NiFe2O4 composite nanostructures with excellent light response and magnetic performance synthesized toward enhanced photocatalytic activity. Issue 35 (18th August 2015) - Jing, Panpan; Du, JinLu; Wang, Jianbo; Lan, Wei; Pan, Lining; Li, Jianan; Wei, Jinwu; Cao, Derang; Zhang, Xinlei; Zhao, Chenbo; Liu, Qingfang
Abstract : Being capable of gathering advanced properties of SrTiO3 and NiFe2 O4, hierarchical SrTiO3 /NiFe2 O4 composite nanostructures have been synthesized toward enhanced photocatalytic activity. Abstract : Being capable of gathering advanced optical, electrical and magnetic properties originating from different components, multifunctional composite nanomaterials have been of concern increasingly. Herein, we have successfully demonstrated the preparation of SrTiO3 /NiFe2 O4 porous nanotubes (PNTs) and SrTiO3 /NiFe2 O4 particle-in-tubes (PITs) via a single-spinneret electrospinning and a side-by-side-spinneret electrospinning, respectively. The products were characterized by using scanning electron microscopy, transmission electron microscopy, X-ray diffraction, UV-visible diffuse reflectance spectra and a vibrating sample magnetometer in detail. The results indicate that SrTiO3 /NiFe2 O4 PNTs are the heterojunction nanotubes by connecting perovskite SrTiO3 and spinel NiFe2 O4 nanoparticles, but SrTiO3 /NiFe2 O4 PITs are the self-assembled core/shell structures by embedding SrTiO3 nanoparticles into NiFe2 O4 nanotubes. Compared with pure SrTiO3 nanofibers, the two SrTiO3 /NiFe2 O4 composites exhibit a powerful light response and excellent room temperature ferromagnetism. The magnetic separations directly reveal that such amazing recycling efficiencies of about 95% for SrTiO3 /NiFe2 O4 PNTs and about 99.5% for SrTiO3 /NiFe2 O4 PITs are obtained. Furthermore, both the magnetic composites perform considerable photocatalytic activity in the degradation of rhodamine B. We propose that Kirkendall-diffusion and phase-separation are probably responsible for the formation of SrTiO3 /NiFe2 O4 PITs, and this work could provide a feasible way to assemble the core/shell structures of different materials.